Model Pengembangan Kurikulum dan Proses Belajar-Mengajar di ITB dalam Mencetak Teknoprener bagi Kemajuan Bangsa Indonesia dan Pembangunan Nasional Berkelanjutan - Anggiat BP Sinaga (Jurnal Sosioteknologi, 2006)
Currently, national education system is still incapable to provide meaningful contribution to the advancement of Indonesia's nation. It is mirrored on the teaching system at ITB, education here can not forge learners to become agents of innovation for development & prosperity to the Indonesian-national community. Refferring to "Development on Humanity Science at ITB (EG-HSc=Expert Group on Humanity Science, 2006)", the students' perception is, that lecture-units furnisked by the department (study programe) are yet to keep-up in defining graduates toward modernization agents. Hereby, an educational-direction still obscures itself in turning-out graduates. Either they would be directed for managerial or, prepared to be workers. On the other hands ITB's students are relucant to leave "secured-zone". Which is, to be employed by enterproses or institutions rather than cretae/expand employments. Based on abalysis of Sociotechnology Department's Lab. (SocTec Laboratory, ABPS et, al., 2006), the students' essential-needs, are abilities to become innovative agents by forming thought-pattern, comprehension & absorption over what to do. How to act & solve in anticipating the risks when it is carried-out. In this context, lecture-units-curricullum, SAP & Syllabus-given to the students are closely linked to searching solution & way of actions. In solving/anticipating diverse problems amidst Indonesia's National society, nowadays & in the future.